Simulação numérica de escoamento liquido-sólido de fluído viscoplástico em seção anular com acoplamento CFD-DEM - Gemeli, Joana Leonardi (2024)
The description of solid particles movement is of crucial importance in oil well drilling processes, where inefficiency in gravel removal capacity leads to high operational times and increased pressure inside the well. This scenario translates into declines in productivity rates and a significant increase in operational costs. Faced with this challenge, numerical simulations emerge as valuable tools to aid in understanding the involved phenomena. The modeling of viscoplastic fluids flows in the presence of solid particles requires the characterization of the non-Newtonian behavior of the transport fluid, as well as the interactions that occur between particles, and the interaction between the liquid and solid phases. Due to the complexity involved in this type of analysis, there is a noticeable scarcity of data in the scientific literature. The aim of this work is to numerically assess the behavior of liquid-solid flow through the coupling of computational fluid dynamics and the discrete element method (CFD-DEM), analyzing especially the effect of the rheological parameter Herschel-Bulkley fluid power-law index on the behavior of the flow used in transporting solid particles inside an annular section tube. Through the CFD approach, the finite volume method was employed to solve the mass and momentum balance equations of the liquid phase. DEM was used to describe the behavior and interactions of the solid particles, characterizing the lagrangian analysis. Interactions between the liquid phase and solid particles present in the flow field was solved using the CFD-SEM coupling scheme. The calibration necessary for DEM use resulted in a time step of 10, which was used on the simulations. The range of values used for the dimensionless numbers were Reynolds between 44 and 355, Hedstrm from 157 to 1179 and Taylor between 1,14 and 8,58. From the numerical results, it was possible to visualize the bed of solid particles and classify them into different flow regimes. The results also indicate that increasing the rheological properties, yield stress and power-law index, as well as the increase in flow rate, result in an increase in the article loading capacity.